2019
DOI: 10.3390/cancers11071030
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ROS Generated by Chemical, Physical, and Plasma Techniques on Cancer Attenuation

Abstract: For the last few decades, while significant improvements have been achieved in cancer therapy, this family of diseases is still considered one of the deadliest threats to human health. Thus, there is an urgent need to find novel strategies in order to tackle this vital medical issue. One of the most pivotal causes of cancer initiation is the presence of reactive oxygen species (ROS) inside the body. Interestingly, on the other hand, high doses of ROS possess the capability to damage malignant cells. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(94 citation statements)
references
References 266 publications
(277 reference statements)
1
93
0
Order By: Relevance
“…High levels of ROS can activate pro-survival pathways, leading to DNA damage, genomic instability, metabolic alterations, and drug resistance [19]. In cancer cells, intracellular ROS level undergoes a sophisticated regulation by multiple mechanisms (detailed in Section 2.1) and, therapeutically, their excess may sensitize tumor cells to chemotherapy [21]. In this regard, drug treatments usually trigger a further increase of ROS that may exhaust the cellular antioxidant capacity, thus leading to cancer cell death.…”
Section: Reactive Oxygen Species: Types and Formationmentioning
confidence: 99%
“…High levels of ROS can activate pro-survival pathways, leading to DNA damage, genomic instability, metabolic alterations, and drug resistance [19]. In cancer cells, intracellular ROS level undergoes a sophisticated regulation by multiple mechanisms (detailed in Section 2.1) and, therapeutically, their excess may sensitize tumor cells to chemotherapy [21]. In this regard, drug treatments usually trigger a further increase of ROS that may exhaust the cellular antioxidant capacity, thus leading to cancer cell death.…”
Section: Reactive Oxygen Species: Types and Formationmentioning
confidence: 99%
“…The generation of radicals within the gas, liquid, and solid interfaces are known to be the main triggers of CAP effects primarily linked to inhibition of cell proliferation and cell death [14][15][16]19]. Interestingly, by using electron spin resonance (ESR) spectroscopy, our research group recently showed that MABS was characterized by an 18-fold higher increase of total spin density generated within 10 s of treatment when compared to that of the CAP device kINPen med [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…CAP treatment led to sufficient inhibition of cancer cell growth, interestingly, without tissue swelling, inflammation, or pain. Growing evidence points towards reactive oxygen and nitrogen species (RONS) as being primarily responsible for CAP-triggered cell mechanisms and cell death [13][14][15][16]. Other highly reactive components of CAP include diverse charged particles, free radicals, and ultraviolet and infrared radiation [17].…”
Section: Introductionmentioning
confidence: 99%
“…SELENOS-knockdown cell lines grew faster than control cells, and SELENOS(U188C) expression did not affect cell growth. As ROS can initiate and prevent cancer development (Mitra et al, 2019), there might be a relationship between the increased U2OS cell growth and the reduced ROS level. Together, these findings indicated the importance of mature SELENOS for ROS production and cell growth.…”
Section: Ros Production Is Decreased By Downregulating Selenos In U2omentioning
confidence: 99%